1990
DOI: 10.1002/path.1711610111
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study of Helicobacter pylori‐associated gastritis

Abstract: Endoscopic biopsies of antral mucosa from 26 patients with Helicobacter pylori-associated gastritis were studied by electron microscopy (EM). Scanning electron microscopy (SEM) showed clustering of H. pylori in the intercellular areas, being entrapped by the microvilli which were decreased at the sites where the bacilli were seen. The observations of SEM were confirmed by transmission electron microscopy (TEM), which showed adherence of the bacilli to the cell surface, producing cup-shaped depressions in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
2

Year Published

1993
1993
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 17 publications
1
37
2
Order By: Relevance
“…Thomsen et al (7) could demonstrate only loose attachment of the organisms and suggested that cell adherence is probably not an important virulence trait. In contrast, most other studies, using scanning or transmission electron microscopy, were able to show various forms of firm attachment between H. pylori and gastric cells, often resulting in deformation, blunting or focal ablation of gastric microvilli (8,12,15,17,23). This was comparable to, but possibly biochemically different from, the ''attaching-effacing'' effect observed with E. coli strains carrying the eae-gene (EPEC-strains; 12,17).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Thomsen et al (7) could demonstrate only loose attachment of the organisms and suggested that cell adherence is probably not an important virulence trait. In contrast, most other studies, using scanning or transmission electron microscopy, were able to show various forms of firm attachment between H. pylori and gastric cells, often resulting in deformation, blunting or focal ablation of gastric microvilli (8,12,15,17,23). This was comparable to, but possibly biochemically different from, the ''attaching-effacing'' effect observed with E. coli strains carrying the eae-gene (EPEC-strains; 12,17).…”
Section: Discussionmentioning
confidence: 74%
“…However, the results have often been discordant and in part difficult to interpret: different study models were applied, involving animal cells (14), cultured human gastric cells (9), gastric cancer cell lines (17, 21, 31), as well as tumour cell lines of other origin (18,19,22). Some investigations used live cells from patients with dyspepsia (3, 10) or gastritis (5,7,8,11,13), and only a few have included test materials from patients with gastric or duodenal ulcers (6,20). Studying adherence of H. pylori using cell lines, especially of non-gastric origin, has obvious limitations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations